Proprotein Convertases - Mbikay, Majambu.; Mbikay, Majambu.; Seidah, Nabil G.; Seidah, Nabil G. (Methods in Molecular Biology,, 2011)
Today, activation endoproteolysis of secretory proteins is recognized as a fundamental biological mechanism of spatial and temporal regulation of protein activity as well as of diversification of protein functions.  In Proprotein Convertases, experts in the field examine detailed methods involving proprotein convertases, the enzymes mediating this endoproteolysis, which reside within or cycle between the various compartments of the secretory pathway.  Providing a timely assessment of impact of activation/inactivation endoproteolysis in the secretory pathway, the volume offers a broader perspective on the biochemistry of the PCSKs (proprotein convertases, subtilisin/kexin-type) by exploring structural and functional analogies with bacterial subtilisin and on the enzymology of endoproteolysis itself by describing the involvement in the process of non-PCSK-type such as cathepsin L.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their specific topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Meticulous and up-to-date, Proprotein Convertases represents an instructive and useful reference book for all scientists interested in endoproteolytic activation and/or inactivation of secretory proproteins through limited proteolysis, for experts in the field and newcomers to it as well.